Fraud Prevention Through Internal Control and Moral Sensitivity (A Case Study at State-Owned Banks) - Ricky; Chairul Insani; Mahdi; Deni Riani; Asri Ady Bakri (Ilomata International Journal of Management, 2023)
Fraudulent behavior includes any unethical or harmful behavior that affects people, organizations, and environment. The purpose of this study is to examine how internal control, as well as sensitivity and morality can prevent fraud from occurring. There are four state-owned banks participating in this study. To collect the data, questionnaires were distributed to and completed by 100 workers of state-owned banks. Additionally, this study implemented multiple linear regression analysis as its methodology. The findings of this study demonstrate that internal control has a positive and significant impact on preventing fraud with a t count > t table, specifically 4.239 > 1.66023 with a significance value of 0.000, less than 0.05, and moral sensitivity has a positive and significant impact on preventing fraud with a t count > t table, specifically 1.998 > 1.66023 with a significance value of 0.048, less than 0.05.